Design, synthesis, 2D-QSAR, molecular dynamic simulation, and biological evaluation of topiramate-phenolic acid conjugates as PPARγ inhibitors - Ipsa Padhy; Biswajit Banerjee; P. Ganga Raju Achary; Pramodkumar P. Gupta; Tripti Sharma (SpringerOpen, 2024)
Abstract Background Obesity is a precursor for many co-morbid diseases. One of the main triggering factors for obesity is the abnormal expansion of white adipose tissue characterized by high rates of genesis and differentiation of precursor cells into mature adipocytes. As a result, targeting adipogenesis and adipogenic transcription factors opens new roadmaps for developing novel antiobesity pharmacotherapies. The present study was intended to rationally develop topiramate-phenolic acid conjugate for targeting obesity via inhibition of PPARγ which is often considered as the master regulator of adipogenesis. Results 2D QSAR models were built to foretell PPARγ inhibitory activity of designed conjugates. The models presented excellent robustness, goodness of fit, and predictive capability compounds. The highest PPARγ inhibitory activity was predicted for T3 (topiramate-caffeic acid conjugate) with a pIC50 value of 7.08 µM. Molecular docking was performed for all the designed conjugates against PPARγ (PDB ID: 3VSO). The highest binding affinity was exhibited by T3 (− 11.27 kcal/mol) and displayed strong and stable interactions with the receptor within the allosteric pocket in comparison to the irreversible PPARγ antagonist, GW9662 (binding affinity, − 9.0 kcal/mol). These results were confirmed by subjecting the best-docked molecules to molecular dynamic simulations. The PPARγ-T3 complex was observed to be most stable with maximum number of hydrogen bonds (maximum observed RMSD = 0.57 Å at 100 ns) in comparison to PPARγ-topiramate and PPARγ-caffeic acid complexes. Consequently, T3 was synthesized and further subjected to in vitro screening. The TR-FRET assay established T3 as a PPARγ antagonist (IC50 = 6.78 µM). T3 also significantly reduced the lipid buildup in the 3T3-L1 adipocytes in a dose-dependent manner. In addition, T3 also reduced the protein expression levels of PPARγ as evidenced from western blot results. Conclusions Studies clearly indicated that T3 reduces adipose tissue cell differentiation by downstreaming PPARγ expression at protein levels, thereby emerging as a novel scaffold for antiobesity pharmacotherapy. Graphical abstract